The Ethics of AI in Latin America. Approaches to the Use and Regulation of Artificial Intelligence in the Contemporary ANA Region - Benedikter, Roland (Studi Politici, 2025)
This article provides a review of the socio-economic implications introduced by the use of AI in contemporary Latin America. The potential of this technology is linked to the geopolitical dynamic related to the recent polarization of globalization and the resulting international alignments and non-alignments. In particular, the article focuses on the role of Latin America within an ANA (actively non-aligned) framework, which is increasingly gaining traction among the countries involved. This vision of non-alignment is particularly significant as it offers Latin American nations an opportunity to navigate the global geopolitical landscape without being overly reliant on major powers, thereby allowing them to pursue a more independent path in shaping their futures. The article highlights the development opportunities that AI presents to the countries involved, emphasizing how the technology can serve as a tool for economic transformation, noting the ethical issues and social challenges that come with it.